DISKURSUS ISLAM KONTEMPORER - Yusdani Yusdani; M. Roem Syibli (Millah: Journal of Religious Studies, 2009)
The research below tries to investigate the trend of  Islamic discourse and writing  structure of  bulletins published every Friday in Yogyakarta Special Territory. The research constitutes descriptive and survey methods based on religiousity and sociological approaches. The data are obtained from  six different bulletins namely al-Ikhtilaf al-Rasikh, al-I’tishom, al-Ikhlas, at-Tauhid, and Risalah Jumat. The result revealed that the bulletins distributed in Yogyakarta are generally categorized as substantive either in its paragraph, content, closing paragraph or in their Islamicity discourse.